Complexation between darunavir ethanolate and beta cyclodextrin: experimental and theoretical studies - Kogawa, Ana Carolina [UNESP]; Zoppi, Ariana; Quevedo, Mario Alfredo; Longhi, Marcela Raquel; Salgado, Hérida Regina Nunes [UNESP] (My University, 2014)
Darunavir (DRV) is a protease inhibitor used in the treatment of HIV infection, which constitutes a keystone in the therapy of patients infected with this virus. Unfortunately, DRV has low solubility in water and poor bioavailability, therefore it requires administration in relatively high doses in order to exhibit therapeutic efficacy. A commonly applied approach to increase the solubility of drugs is the formation of complexes with macromolecules, of which molecular encapsulation with β-cyclodextrin (βCD) constitutes an alternative for the development of new pharmaceutical dosage forms. Therefore, it was to evaluate by theoretical (molecular modelling) and experimental (spectroscopic) approaches the possibility of obtaining an inclusion complex between DRV and βCD. From the results obtained by the docking procedures, we found three clusters of conformations for the DRV:β-CD complex, corresponding to conformations in which the ligand moieties were buried into the β-CD hydrophobic cavities. Molecular modelling results were compared with spectroscopic studies, with 1H NMR studies evidencing that DRV and βCD proton resonances were modified upon complexation, thus confirming the formation of the inclusion complex. The combination of theoretical and experimental techniques confirmed the formation of the inclusion complex between DRV and βCD.
Keywords: β-cyclodextrin; Complexation; Darunavir ethanolate; Molecular modeling; Protease inhibitor; Spectroscopic studies